Reference intervals of complete blood count parameters for individuals aged 80 to 89 years in Guizhou, China: A STROBE-compliant retrospective study. Issue 40 (7th October 2022) - Long, Jinlie; Wang, Xiuhong; Yuan, Jianbo; Yang, Jianru; Zhou, Jie; Chen, Yuan; Hu, Enxi; Zhou, Yuanzhong; Min, Xun
Abstract : The reference intervals of complete blood count (CBC) parameters were commonly based on healthy individuals aged 20 to 79 years. However, these values are not optimal for correct clinical diagnosis in older individuals (e.g., 80–89 years). Although the reference intervals for this age group have been reported in China, there is no population-based report in Guizhou province. A total of 481 healthy adults (238 males and 243 females) aged 80 to 89 years were recruited from Affiliated Hospital of Zunyi Medical University in Guizhou. The CBC parameters were detected by Sysmex XN-9000 automatic hematology analyzer. The reference intervals of the components were analyzed according to the guidelines of International Federation of Clinical Chemistry. This study reported the reference intervals of CBC parameters. There were significant differences were examined in some reference intervals between the different gender groups, especially for RBC-related parameters. Compared with national standards, the most of all conventional reference intervals for CBC parameters were decreased. The present study provided the local reference intervals of CBC parameters for individuals aged 80 to 89 years in Guizhou, China. Some of our results were sex-specific, and most of our results show lower values while comparing with commonly used reference intervals in China. Therefore, more attentions should be paid to these differences, and accurate reference intervals will facilitate clinical diagnosis and decision-making in these populations.